Career maturity among gifted and talented students in Malaysia - Hakimie Zainal Abidin, Mohd; Amat, Salleh; Subhan, Mhd; Izwan Mahmud, Mohd; Ali, Sallehuddin; Yazid Abu Bakar, Abu (International Journal of Engineering and Technology, 2018)
Career maturity is one of the crucial element for students in the school setting. Career maturity is vital for students to discover their knowledge about their future professions. For gifted and talented students, they may advance from the regular students in discovering their future jobs. This study focusing on career maturity among gifted and talented students in Malaysia. The level of career maturity is measured by the researcher by using Career Maturity Inventory (CMI)-Revised 1995. This research involved 2500 respondents around Malaysia, focusing on boarding schoolsâ€™ students. The descriptive statistical analysis is used to present the demographic data involving gender, the level of education, and family income of the respondents.Â  The main finding of this research indicates the difference in career maturity between respondents (gifted and talented students) and the regular students. The implications of this research are discussed especially in terms of guidance and counseling provision in boarding school.Â